Ascites in Broiler Chickens - ., Tarmudji (Indonesian Animal Sciences Society, 2005)
Ascites is a common problem among rapidly growing broiler strains of chickens . This incidence is most often associated with heart failure . This problem is started from insufficient of lung volume or lung capillary capacity for oxygen exchange in very fast growing broiler chickens . Pulmonary hypertension syndrome (PHS) occurs due to the increased blood flow in the lung, causing a hypertrophy an the right ventricular a valvular insufficiency, an increased vena pressure and finally a ascites . Genetically, the percentage of lung volume to the body weight in broiler chickens which is too small is a predisposition factor in ascites cases . The air sac capacity which is decreasing due to the pressure form the intestine parts, the heavy breast and lives mass causes broilers are more sensitive to PHS . Some factors that contribute to PHS are management (high density, pelleted food, superior feed), environment (high altitude of location, cold, moderate, low oxygen) and physiology (increased of oxygen requirements, hyperthyroidism and respiratory disease) . The ascites mechanism could be described as a circle of events between the cardiac, pulmonary and vascular system that satisfy the metabolic requirement of the bird. Lack of one of these systems triggers the pathological cascade that results in ascites cases . Key words: Ascites, broiler chickens, pulmonary hypertension syndrome . heart failure